Survey on Technical Efficacy of the Farmers and Their Satisfaction Level for the Production of Onion Seeds in Bagmara Upazila, Rajshahi District (Research in Agriculture Livestock and Fisheries, 2020)
Onion seed production is not exactly same as the cultivation of the onion as a crop. Due to lack of recommended standard cultural practices, an onion seed producer in Bangladesh is facing different levels of difficulties. To address this issue, the present study has been undertaken for generating farm level information on the production and input use pattern in the onion seed cultivation. Using semi structured questionnaire, a total of 50 onion farmers is randomly selected from Bagmara upazila, Rajshahi district for the interview. The results indicate that there were so many constraints on onion seeds production such as unavailability of high yielding varieties, shortage of information about recommended fertilizer doses, bulb size, planting space, setting of planting time, etc. At the same time, farmers are also fronting problem regarding paucity of separated land, absence of specialized onion cold storages. Considering the above- mentioned problems, the results showed that 70% of the farmers are not satisfied with the onion seeds yield. The study suggested that distribution system of the quality onion seeds has to be improved coupled with the onion research in Bangladesh has to govern by the dynamics of seed grower’s quality preferences and their socio- eco- climatic infrastructure. Furthermore, it is indispensable to introduce training programs for the farmers for improving their knowledge about management practices as seed production required highly skill personRes. Agric., Livest. Fish.7(3): 383-391,  December 2020